The Influence of Health Consciousness and E-Service Quality on Traditional Medicine Purchasing Decisions (Case Study of CV Dari Teman Sejati) - Diningrat, Yosiah Tutus Angriawan Jaya; Krispimandoyo, Denpharanto Agung (Universitas Ciputra Surabaya, 2023)
The purpose of this research is to examine and analyze the influence of health consciousness and e-service quality on the purchasing decisions of traditional medicines. The background to this research stems from the discovery of the phenomenon of increasing health awareness in the community but sales to companies are experiencing a downward trend. In addition, in the digital era where people are active in transacting online to meet their needs, companies are interested in developing distribution through e-commerce. The company also wants to develop a new market through a new product, Teki Tea for menstrual pain. Therefore, in this study the respondents who were focused were women aged 15-29 years, with the criteria of having bought traditional medicine online. Total respondents were 154 with data collection through questionnaires and processed using SPSS software. The results of this study indicate that health consciousness and e-service quality have a positive and significant effect on the decision to purchase traditional medicines.